Analisis Ketersediaan dan Persebaran Layanan Pendidikan SMA di Kabupaten Purbalingga Ditinjau dari Kebijakan Sistem Zonasi Sekolah - Fanda Astrianingrum; Sutomo Sutomo; Dhi Bramasta (UM Purwokerto Press, 2022)
Education is one of the human needs to be able to process and interact in the outside world with all the surrounding communities. Education is one of the main things that must be considered because education is able to shape everyone's personal character if they are serious about it. Based on Government Regulation No. 47 of 2008 concerning Compulsory Education, article 1 paragraph 1 states that compulsory education is a minimum education program that must be followed by Indonesian citizens on the responsibility of the Government and Local Government. To increase the 12-year compulsory education, it is necessary to provide adequate educational services, but this has not been fulfilled because the increase in the number of students entering school is not proportional to the number of existing schools. The zoning sistem is a sistem that regulates the acceptance of new students. Based on the Regulation of the Minister of Education and Culture as stated in the Regulation of the Minister of Education and Culture Number 20 of 2019 concerning amendments to Permendikbud number 51 of 2018 concerning the Admission of New Students in Kindergarten, Elementary School, Junior High School, Senior High School , and Vocational High School with a zoning sistem. By implementing a zoning sistem, schools are required to accept prospective students through the zoning route, 90% of the total quota, 5% is used for the achievement route, and 5% is used for the transfer of parents.Purbalingga Regency is one of the regencies in Central Java Province. This district consists of 18 sub-districts, the center of government is in Purbalingga District. Based on Article 1 of the 2003 National Education Sistem Law education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential. To find out the availability and distribution of Education Services in the scope of Senior High School in Purbalingga district in 2022 based on the school zoning sistem, Senior High School education services with public and private status have been spread thoroughly in Purbalingga Regency with the stipulation of a Zoning Sistem Policy with the hope of improving education equity. For this reason, researchers are interested in conducting further research with the desire to know more deeply the issue of